THE LEGAL NATURE OF CRIMES IN THE SPHERE OF TERRORISM AND INTERNATIONAL LEGAL INSTRUMENTS TO COMBAT THEM - Rybak, Siarhei (Administrative and Criminal Justice, 2019)
The paper deals with the issues of combating terrorism. The authors draw a distinction between the concepts of “international crime” and “crime of an international character”. Particular attention is paid to the lack of a universal definition of the category of “terrorism’s” problem and its reasons. A new vision of the solution to the problem mentioned above has been offered. The paper also analyzes the international regulatory legal acts regulating the struggle against terrorism and their impact on the formation of national legislation in the designated area.